Ischemic postconditioning reduced myocardial ischemia-reperfusion injury: The roles of melatonin and uncoupling protein 3 - Aslan, Gulnur; Gul, Huseyin Fatih; Tektemur, Ahmet; Sahna, Engin (Turkish Soc Cardiology, 2020)
Objective: Protective effects of ischemic postconditioning (PostC) decrease/disappear with age and chronic heart diseases. Similarly, low serum melatonin levels have been reported in the same risk groups. The aims of this study were to investigate the effects of melatonin on the protection of PostC in ischemia-reperfusion (I/R)-induced infarct size and roles of uncoupling protein (UCP) 3, irisin, and nuclear factor kappa B (NFkB) levels. Methods: Rats were pinealectomized (Px) or sham operated (non-Px) 2 months before the I/R studies. The left main coronary artery was occluded for 30 min followed by 120 min reperfusion. PostC was induced with three cycles of R/I (10 s each) after ischemia. Results: The infarct size was found to be significantly higher in Px rats (54.68 +/- 1.5%) than in the control group (35.1 +/- 2.5%). PostC and melatonin administrations to non-Px rats significantly reduced the infarct size. On the other hand, PostC did not create a significant effect in Px rats, but protection was provided when PostC was co-administrated with melatonin. While significant decreases were detected in the UCP3 levels, irisin and NFkB levels increased with I/R and Px. Treatment with PostC and melatonin in non-Px groups and their co-administration in Px groups were found to return all the genes close to normal levels. Conclusion: The physiological and pharmacological concentrations of melatonin may play a role in the protection of PostC. In cases when physiological melatonin is reduced, such as aging and heart diseases, this protection may decrease, and this effect may be restored by melatonin replacement. PostC and melatonin may regulate energy metabolism and inflammatory mediators and protect mitochondria by affecting the UCP3, irisin, and NFkB levels.
Miyokardiyal iskemi-reperfüzyon hasarında ardkoşullanmanın koruyuculuğunda melatoninin fizyolojik ve farmakolojik konsantrasyonlarının rolü
Keywords: reperfusion injury; postconditioning; melatonin; uncoupling protein 3; irisin; nuclear factor kappa B